Pengaruh Model Pembelajaran Kooperatif Tipe Make A Match Berbantuan Aplikasi 3D terhadap Pemahaman Konsep pada Materi Sistem Pencernaan - Khairanti, Dita; Khairuna, Khairuna (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
This research utilized a cooperative learning model of make a match type assisted by a 3D application to investigate the influence of students' conceptual understanding on the topic of the digestive system in Grade XI of a Private High School in Medan City. The objectives of this study were to determine the impact of using the cooperative learning model of make a match type assisted by a 3D application and to assess students' conceptual understanding of the digestive system material. The research design employed was a non-equivalent control group quasi-experimental approach with a quantitative method. The study was conducted with an experimental group and a control group. The instruments administered to both groups consisted of pretest (before treatment) and posttest (after treatment) essay questions adjusted according to conceptual understanding indicators. Data analysis included descriptive statistical approach, inferential analysis, and independent t-test hypothesis testing to evaluate the influence and differences in students' conceptual understanding between the experimental group (treatment) and the control group using conventional learning models. The results of this study indicated that the posttest scores in the experimental group increased by 73.95 points, compared to only 12.19 points in the control group. The findings suggest a significant impact of the treatment (experimental group) on students' conceptual understanding of the digestive system material in one of the Private High Schools in Medan City.